ADEQUATENESS OF APPLYING MODELS TO PREDICT POTENTIAL FINANCIAL DISTRESS - Rane, Jayantkumar Vijay; Kanetkar, Medha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research examines the financial stability of Non-Banking Financial Companies (NBFCs), which are crucial players in the economy but also pose inherent risks due to their unique operational structures. Given the increasing concerns regarding financial distress and bankruptcy within this sector, effective regulation and predictive analysis are essential. The study evaluates the applicability of two established bankruptcy prediction models—Altman’s Z-Score and Springate’s Z-Score—in assessing the financial risks faced by NBFCs. These models use financial ratios to predict bankruptcy and assist stakeholders in decision-making. In addition to these traditional models, the research introduces a new model, the Financial Distress Index (FDI) Z-Score, which improves the prediction of financial distress by incorporating a broader set of financial indicators. The FDI Z-Score enhances the understanding of financial risk in NBFCs by considering additional factors such as corporate governance, market sentiment, and risk-weighted assets. This model offers a more comprehensive approach to predicting financial instability compared to existing models. The findings show that both Altman’s Z-Score and Springate’s Z-Score provide strong predictive capabilities in identifying financial distress, with accuracy rates of 70%-75% in forecasting bankruptcy up to three years in advance. The study concludes by advocating for the adoption of these predictive models, particularly the FDI Z-Score, to effectively monitor and manage financial risks in NBFCs. This research contributes to the broader understanding of financial distress prediction and provides valuable insights for regulatory authorities, investors, and other stakeholders in the NBFC sector.Keywords: Financial Distress, Financial Instability, Bankruptcy, NBFCs, Shadow Banking Altman’s Z Score, Springate Z Score,